Illuminating Chinese EFL student teachers' paradoxical perceptions of theory learning experiences. Issue 1 (2nd January 2022) - Yan, Chunmei; He, Chuanjun
ABSTRACT: Theory-practice gap has been a long-standing challenge in teacher education, however, there has been scarce attention to student teachers' theory learning experiences. This ethnographic study aimed to examine Chinese EFL (English as a foreign language) M.E.d. student teachers' perceptions of the value of theory and their experiences of theory learning on the Master of Education programme. Four triangulated sources of data were employed, including student teachers' portfolios of written responses to academic papers and reflections on their two-stage school experiences, longitudinal participant observations, course evaluations, and focus groups. It was found that the student teachers held paradoxical perceptions about theory learning. They endorsed the importance of theories, but resisted the mainstream theory learning methods which heavily relied on de-contextualised lecturing by teacher educators. To enhance student teachers' theory learning experiences requires teacher educators' overall instructional transformations, increased opportunities for reflective learning-to-teach experiences, and student teachers' attitudinal change and sustained efforts.